Peran Mahasiswa Kuliah Kerja Nyata (KKN) dalam Upaya Pencegahan dan Penanggulangan Stunting Melalui Pemberian Makanan Bergizi dan Vitamin Kepada Anak-Anak di Desa Bahaur - Ahmad Saufi; Nor Elisa; Ulma Aprilianti; Annisa Utami; Masita Nurul Aini; Mayada Azzahra; Muhammad Dzakil Amin; Sri Hidayati (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Stunting is a serious problem because it affects the growth of children. Various places experience stunting problems, one of which is Bahaur Village. In this village, stunting is an unresolved problem. Therefore, the purpose of this community service is for KKN students to collaborate with the village government to run stunting prevention programs such as posyandu, providing nutritious food and vitamins. The result of this service is that the community participates to help prevent the continuation of this stunting problem in children, and participates in posyandu activities regularly to get vitamins and nutritious food to prevent stunting.